Interaction Effects of Inflation Accounting Models and Accounting Techniques. - McIntyre, Edward V. (The Accounting Review, 1982)
ABSTRACT: Choices of accounting techniques, as well as evaluations of accounting numbers, are based in part upon a knowledge of the relative profit patterns associated with alternative techniques. It is generally understood that inflation accounting models change profit patterns, and the general effects of changes from historical cost accounting to various inflation accounting models have been analyzed. In addition to these general effects, however, there are specific effects due to the interactions of conventional accounting techniques (such as LIFO and FIFO) and specific inflation accounting models. This study analyzes the interaction effects of conventional inventory accounting methods and several inflation accounting models to demonstrate that these effects can produce significant and non-intuitive changes in relative profit patterns among alternative accounting techniques.